Anti‐Inflammatory Effect of Quercetin on RAW 264.7 Mouse Macrophages Induced with Polyinosinic‐Polycytidylic Acid - Young‐Jin Kim; Wansu Park (Molecules, 2016)
Quercetin (3,3′,4′,5,6‐pentahydroxyflavone) is a well‐known antioxidant and a flavonol found in many fruits, leaves, and vegetables. Quercetin also has known anti‐inflammatory effects on lipopolysaccharide‐induced macrophages. However, the effects of quercetin on virus‐induced macrophages have not been fully reported. In this study, the anti‐inflammatory effect of quercetin on double‐stranded RNA (dsRNA)‐induced macrophages was examined. Quercetin at concentrations up to 50 μM significantly inhibited the production of NO, IL‐6, MCP‐1, IP‐10, RANTES, GM‐CSF, G‐CSF, TNF‐α, LIF, LIX, and VEGF as well as calcium release in dsRNA (50 μg/mL of polyinosinic‐polycytidylic acid)‐induced RAW 264.7 mouse macrophages (p < 0.05). Quercetin at concentrations up to 50 μM also significantly inhibited mRNA expression of signal transducer and activated transcription 1 (STAT1) and STAT3 in dsRNA‐induced RAW 264.7 cells (p < 0.05). In conclusion, quercetin had alleviating effects on viral inflammation based on inhibition of NO, cytokines, chemokines, and growth factors in dsRNA‐induced macrophages via the calcium‐STAT pathway.